On fair interference management in cognitive radio networks - Musab, Muhammad; Ali, Zain; Furqan, Haji Muhammad; Amanat, Irtiza; Jabeen, Tayyaba; Sidhu, Guftaar Ahmad Sardar (Institute of Electrical and Electronics Engineers Inc., 2017)
In this paper, we consider power optimization problem in cognitive radio (CR) networks. The aim is to protect the licensed primary users (PUs) from unequal performance degradation by secondary users (SUs). A min-max optimization problem is formulated to minimize the maximum interference subject to transmission power constraint at base station (BS) and the individual interference constraint at each SU. Further, to guarantee the minimum quality of service (QoS) of each SU, a rate constraint per SU is considered in the problem. Based on convex optimization techniques, a step wise approach is adopted where first the sum interference is minimized and later the sum rate is maximized subject to various constraints.